A return to Turner: Liminalities in Afrikaner identity politics after apartheid - van der Waal, Kees (C. S.) (Anthropology Southern Africa, 2011)
This article explores interpretive possibilities offered by the concept of liminality in the context of identity politics in South Africa in an attempt to build on the rich and stimulating work of Victor Turner towards a comparative and contextual analysis. Degrees and variations of liminality are identified; I am interested, for instance, in whether it is part of hegemonic domination or tactical resistance, historically structured or innovative, and how it is related to class, gender and race in order to go beyond structural positions and social categories. After looking at the current South African transition as a liminal phase, manifestations of Afrikaner/Afrikaans cultural politics are investigated on the level of individual and collective liminality, drawing from the literature, fieldwork and personal experience. With regard to individual and social identity based on Afrikaans, liminality appears, under certain conditions, as either a form of defensive victimhood or as social connectedness and creolisation.